Suppressive subtractive hybridization analysis of Rhipicephalus (Boophilus) microplus larval and adult transcript expression during attachment and feeding - Lew-Tabor, A.; Moolhuijzen, Paula; Vance, M.; Kurscheid, S.; Valle, M.; Jarrett, S.; Minchin, C.; Jackson, L.; Jonsson, N.; Bellgard, M.; Guerrero, F. (Elsevier Science, 2010)
Ticks, as blood-feeding ectoparasites, affect their hosts both directly and as vectors of viral, bacterial and protozoal diseases. The tick's mode of feeding means it must maintain intimate contact with the host in the face of host defensive responses for a prolonged time. The parasite-host interactions are characterized by the host response and parasite counter-response which result in a highly complex biological system that is barely understood. We conducted transcriptomic analyses utilizing suppressive subtractive hybridization (SSH) to identify transcripts associated with host attachment and feeding of larval, adult female and adult male ticks. Five SSH libraries resulted in 511 clones (assembled into 36 contigs and 90 singletons) from differentially expressed transcripts isolated from unattached frustrated larvae (95), feeding larvae (159), unattached frustrated adult female ticks (68), feeding adult female ticks (95) and male adult ticks (94 clones). Unattached 'frustrated' ticks were held in fabric bags affixed to cattle for up to 24 h to identify genes up-regulated prior to host penetration. Sequence analysis was based on BLAST, Panther, KOG and domain (CDD) analyses to assign functional groups for proteins including: cuticle proteins, enzymes (ATPases), ligand binding (histamine binding), molecular chaperone (prefoldin), nucleic acid binding (ribosomal proteins), putative salivary proteins, serine proteases, stress response (heat shock, glycine rich) and transporters. An additional 63% of all contigs and singletons were novel R. microplus transcripts or predicted proteins of unknown function. Expression was confirmed using quantitative real time PCR analysis of selected transcripts. This is the first comprehensive analysis of the R. microplus transcriptome from multiple stages of ticks and assists to elucidate the molecular events during tick attachment and development. Crown Copyright © 2009.